Controller design for a pilot-scale heating and ventilation system using fuzzy logic approach - Mohd. Subha, Nurul Adilla (Penerbit UTM Press, 2011)
In this paper, a Single–input fuzzy logic controller (SIFLC) is designed and applied on a nonlinear heating and ventilation plant VVS-400 developed from Instrutek, Larvik, Norway. VVS–400 is modeled using Auto–regressive with exogenous input (ARX) model structure and linear black–box technique. The proposed SIFLC offers significant reduction in rule inferences and simplify the tuning of control parameters. To verify its effectiveness, this control method is simulated with an approximated VVS–400 model. An approximated VVS–400 model is obtained using System Identification toolbox in Matlab. The SIFLC provides several advantages over conventional fuzzy logic controller (CFLC) due to its simple inference rule mechanism, require very minimum tuning effort and minimizing the computational time to accomplish the controller algorithm. Simulations validate the equivalency of both controllers. Results reveal that SIFLC and CFLC have almost similar output performance. However SIFLC requires very minimum tuning effort and has less computational time.